Genetic diversity in rice (Oryza sativa) genotypes under humid tropics of Andaman based on grain yield and seed characters - ROY, BIDHAN; BASU, A K; MANDAL, A B (The Indian Journal of Agricultural Sciences, 2014)
The nature and magnitude of gcnetic diversity were estimated during the rainy season of 1998, 1999 and 2000 in 50 high-yielding varieties and traditional germplasm office (Oryza sativa L.), under the humid tropics of Andaman using Mahalanobis’ D2 statistics. The gcnotypes were found to be grouped into 10 clusters. The pattern of distribution of genotypes within various clusters was random and independent of geographical origin or rcgion of adaptation. Clusters IV and X were identilied as most diversified groups, followed by IV and IX. Days to 50% flowering, grain length, kernel breadth and grain yield/plant were found to be the major component characters, contributing towards genetic diversity. Based on the mean grain yield performance, genetic distance and clustering pattern intercrossing amongst ’Taipei 309’, ’SIPI 681032’, ’Black Jeera’, ’IR 54447 B-B-B 10-2’ may be used to obtain transgressive segrcgants with high heteriotic effects, which would be appropriate for the development of high-yielding varieties compatible for large-scale cultivation in Bay Islands.